Determining the safety range of electrical pulses for two benthic invertebrates: brown shrimp (Crangon crangon L.) and ragworm (Alitta virens S.). (31st October 2014) - Soetaert, Maarten; Chiers, Koen; Duchateau, Luc; Polet, Hans; Verschueren, Bart; Decostere, Annemie
Abstract: Pulse trawling is currently the most promising alternative for conventional beam trawls targeting sole and shrimp, meeting both the fisher's aspirations and the need for more environmentally friendly fishing techniques. Before electrotrawling can be further developed and implemented on a wider scale, however, more information is needed about the effects of electrical pulses on marine organisms. The organisms used in the present experiments were brown shrimp ( Crangon crangon L.) and king ragworm ( Alita virens S.) as model species for crustaceans and polychaetes, respectively. These animals were exposed to a homogeneously distributed electrical field with varying values of the following parameters: frequency (5–200 Hz), electrical field strength (150–200 V m −1 ), pulse polarity, pulse shape, pulse duration (0.25–1 ms), and exposure time (1–5 s). The goal of this study was to determine the range of safe pulses and thereby also to evaluate the effect of the pulses already being used on commercial electrotrawls. Behaviour during and shortly after exposure, 14-d mortality rates, and gross and histological examination were used to evaluate possible effects. The vast majority of shrimp demonstrated a tail flip response when exposed to electric pulses depending on the frequency, whereas ragworm demonstrated a squirming reaction, independent of the frequency. No significant increase in mortality or injuries was encountered for either species within the range of pulse parameters tested. Examination of the hepatopancreas of shrimp exposed to 200 V m −1 revealed a significantly higher severity of an intranuclear baculoform virus infection. These data reveal a lack of irreversible lesions in ragworm and shrimp as a direct consequence of exposure to electric pulses administered in the laboratory. Despite these promising results, other indirect effects cannot be ruled out and further research hence is warranted.